From autoecology to variability of medics in Algeria: synthesis trial of works realized at the National Agronomic Institute - El Harrach - Abdelguerfi A.; Si Ziani Y.; Kies N.; Ait Ouada M. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
In Algeria, since 1972 numerous works have been realized on phytogenetic resources of forage and pastoral interest. A particular attention has been given to the spontaneous species of genus Medicago in order to introduce them into the fallow and the marginal zones. Within the context of research-training and research-development, many prospectings and collections have been realized and different kinds of works have been carried out on the collected populations of Medicago: autoecology, behaviour, physiology, viral diseases, variability and caryology. The phenological, biometrical and physiological variability have been often studied in relation to the original environmental conditions of the populations. While mentioning the whole work realized, to facilitate access to the information and the targets of these different works, the most important results are indicated.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)